Tipos de juego y la autoestima en niños de la Institución Educativa Inicial Nº 847 Nuestra Señora de la Purísima, Punchana 2022 - Hoyos Falcon, Thadi (2023)
The purpose of the study was to determine the relationship between types of games and self-esteem in infants of the Initial Educational Institution No. 847 Nuestra Señora de la Purísima 2022. The approach of the study was quantitative and its design was non-experimental of a transversal type with a correlational scope. It included a sample population of 97 children from three to five years of age. Observation was used as a technique. The study concluded that the types of games are significantly related to the self-esteem of the children who participated in the study.